Origin of the first-order ferroelectric phase transition in K0.957Li0.043TaO3 solid solution. (December 2016) - Trybuła, Zbigniew; Dec, Jan; Miga, Seweryn; Łoś, Szymon; Trybuła, Małgorzata
Graphical abstract: Highlights: The first-order ferroelectric phase transition in K0.957 Li0.043 TaO3 was detected. A model of the mechanism of the ferroelectricity in K1−x Lix TaO3 is proposed. The coexistence of the relaxor-like and ferroelectric behavior is presented. Non-linear susceptibilities are valuable tools to investigate phase transitions. Abstract: The results of low-temperature linear and nonlinear susceptibilities and polarization measurements of the KLT-4.3%Li crystalline sample are presented. The following model of the mechanism of the ferroelectricity in the K0.957 Li0.043 TaO3 (KLT-4.3%Li) solid solution is proposed. Static quasi-frozen clusters of Li + dipoles affect the ordering process of the remainder of the system: a dynamical correlation of the off-center motions of Ta ions along one of the equivalent off-center sites in the 〈111〉 cubic direction in the octahedral environment of O ions occurs and leads to the formation of a reversible spontaneous polarization.